2016
DOI: 10.1111/1753-0407.12489
|View full text |Cite
|
Sign up to set email alerts
|

Short sleep duration and longer daytime napping are associated with non‐alcoholic fatty liver disease in Chinese adults

Abstract: Short sleep duration and longer daytime napping were associated with an increased risk of prevalent NAFLD in a middle-aged and elderly Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 41 publications
(93 reference statements)
5
47
1
Order By: Relevance
“…To reduce the effect of diabetes, we conducted stratified analysis according to insulin resistance status (yes/no). However, the results showed that the associations between short sleep durations and NAFLD were generally similar across subgroups . We agree with Kawada that there may be a synergistic effect between prolonged napping and short nightly sleep duration.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…To reduce the effect of diabetes, we conducted stratified analysis according to insulin resistance status (yes/no). However, the results showed that the associations between short sleep durations and NAFLD were generally similar across subgroups . We agree with Kawada that there may be a synergistic effect between prolonged napping and short nightly sleep duration.…”
supporting
confidence: 84%
“…We thank Tomoyuki Kawada for his comments in response to our recent article in the Journal of Diabetes entitled “Short sleep duration and longer daytime napping are associated with non‐alcoholic fatty liver disease in Chinese adults,” in which we assessed the association between sleep habit and non‐alcoholic fatty liver disease (NAFLD). Kawada commented on the conclusions and confounding factors in the article.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although most of research has proven a consistent association between sleep and body weight among adults [17,18,19], there are limited studies on the question of these relationships among infants [9,20]. A few studies showed that infants who sleep less than 12 h/d and who have frequent night waking were associated with higher body mass index and increased risks of being overweight at three years old [21,22], while another study showed no significant association between these factors [15].…”
Section: Introductionmentioning
confidence: 99%